Comprehensive Evaluation of Jordanian Companies Performance A Sequential Explanatory Study - Hamzah Al-Mawali Seif; Obeid Al-Shbiel (Journal of Accounting, Business and Management (JABM), 2013)
This study aims to provide comprehensive evaluation of Jordanian service companies' performance by applying mixed methodology, specifically, sequential explanatory approach. The study consist of two many phases; in the first phase, quantitative data obtain from 98 responses from top management of all service companies listed on Amman Stock Exchange (ASE). The results of quantitative phase indicated that all performance dimensions scored mean values above the midpoint score on a 7-point Likert scale measurement. Financial performance scored the highest level, market performance was rated second highest, followed by customer-based performance, which was rated the lowest mean value. The results of the current study drew conclusions regarding the financial and nonfinancial performance of Jordanian services companies that had contributed to the existing research. The second phase was aimed at validating the quantitative results by seven semi structured interviews. The results from the interviews confirmed and explained the results obtained from the quantitative analysis done in the first phase. Academics and practitioners should note the factors which affecting the level of organizational performance in context of Jordan.